2019
DOI: 10.1144/sp487.9
|View full text |Cite
|
Sign up to set email alerts
|

Fracture distribution on the Swift Reservoir Anticline, Montana: Implications for structural and lithological controls on fracture intensity

Abstract: Where primary porosity and permeability of a rock are unfavourable for hydrocarbon production, fractures can improve reservoir potential by enhancing permeability. Higher fracture intensity may create a better-connected fracture network, improving fractured-reservoir quality. Investigations into the controls on fracture intensity commonly conclude that either structural or lithological factors have the greatest influence on fracture abundance. We use the Swift Reservoir Anticline in northwestern Montana to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 58 publications
2
23
1
1
Order By: Relevance
“…In comparison, the folded crest of the structural anticline is much less deformed. This result is contrary to widespread observations that fracture networks in thrusted forced folds are often associated with increasing fold curvature and thus anticlinal crests (Price, 1966;Ericsson et al, 1998;Cosgrove and Ameen, 2000;Fischer and Wilkerson, 2000;Jadoon et al, 2006;Pearce et al, 2011;Watkins et al, 2019;Wang et al, 2020). However some authors have shown that fracture intensity may be highly clustered and is associated with steeply dipping forelimbs but not necessarily with fold crests (Rawnsley et al, 2007;Inigo et al, 2012;Sanderson and Peacock, 2019;Wang et al, 2020).…”
Section: Predicting Fracture System Distribution In the Carbonate Res...contrasting
confidence: 73%
“…In comparison, the folded crest of the structural anticline is much less deformed. This result is contrary to widespread observations that fracture networks in thrusted forced folds are often associated with increasing fold curvature and thus anticlinal crests (Price, 1966;Ericsson et al, 1998;Cosgrove and Ameen, 2000;Fischer and Wilkerson, 2000;Jadoon et al, 2006;Pearce et al, 2011;Watkins et al, 2019;Wang et al, 2020). However some authors have shown that fracture intensity may be highly clustered and is associated with steeply dipping forelimbs but not necessarily with fold crests (Rawnsley et al, 2007;Inigo et al, 2012;Sanderson and Peacock, 2019;Wang et al, 2020).…”
Section: Predicting Fracture System Distribution In the Carbonate Res...contrasting
confidence: 73%
“…따라서 화산력응회암에 비해 응회질 사암 내 상 대적으로 높은 취성 광물 함량이 높은 단열 밀도의 원인 으로 해석된다. 한편 암석 내 공극률이 높을수록 파괴 전 더 많은 모 양변형이 발생할 수 있어 단열의 밀도가 낮아지며 (Corbett et al, 1987;Barbier et al, 2012;Watkins et al, 2019), 또한 구성 입자의 크기가 클수록 단열의 밀도가 낮은 경 향이 있다 (Hanks et al, 1997;Nelson, 2001;Wennberg et al, 2007) (Sanderson and Nixon, 2018). 본 연구에서 수행한 백일도단층 주변 단열 기하 분석 결과는 단열계 연결성에 실질적인 영향을 미치는 요소들의 민감도에 대 한 이해를 증진시킬 수 있다.…”
Section: 단열 자료 획득 및 분석unclassified
“…Three contributions (Burberry et al 2019;McCarthy et al 2019b;Watkins et al 2019) to this volume use the Sawtooth fold-thrust belt of Montana as a well-exposed field example to address questions on how strain partitions in regional-scale fold-thrust structures. This carbonate fold-thrust belt is used by McCarthy et al (2019b) for the application of anisotropic magnetic susceptibility (AMS) analysis to determine strain.…”
Section: Strain and Fractures In Regional-scale Thrust Sheetsmentioning
confidence: 99%
“…McCarthy et al (2019b) conclude that, despite calculations of up to 60% regional shortening in the Sawtooth Range, there is little evidence of a penetrative deformation fabric, with brittle deformation dominating the evolution of the foldthrust belt. This brittle deformation is the subject of the contributions by Watkins et al (2019), who consider the fracture patterns in exposed carbonate beds in the frontal fold structure at the Swift Reservoir Anticline, and by Burberry et al (2019), who take a similar approach for the Teton anticlinea classic locality for the study of fracture sets (Stearns 1964)and the equivalent fold structure along strike to the north. Watkins et al (2019), reaching similar conclusions to those of Czeck et al (2019) based on cleavage refraction, suggest that lithology is the main control on fracture intensity at outcrop, due to the combined factors of porosity and bulk composition, with the structural position on the fold having a limited influence on fracture intensity.…”
Section: Strain and Fractures In Regional-scale Thrust Sheetsmentioning
confidence: 99%
See 1 more Smart Citation